2014
DOI: 10.1007/s11694-014-9204-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mineral element composition of Ayoyo, Baobab and Dandelion vegetable green leaves in Ghana using instrumental neutron activation analysis

Abstract: The present investigation was undertaken to determine the nutritional compositions (mineral elements) of three green leafy vegetable; Dandelion (Taraxacum Officinale), Ayoyo (Corchorus Olitorius) and Baobab (Adasonia Digitata). The ultimate goal is to improve nutrition and health by advocating for increased consumption of indigenous green leafy vegetables with an objective to increasing public acceptance, awareness and utilization. The mineral elements were determined using instrumental neutron activation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Including Baobab leaves in our diets may offer a potential solution for individuals residing in regions with nutrient deficiencies as are a rich source of essential nutrients. More importantly, studies focused on the soil type of Baobab growth as well as regional and ecological differences contribute to the existing literature on Baobab tree products and their value, providing valuable insights for future research and dietary interventions that will be aligned with what was reported by [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 95%
“…Including Baobab leaves in our diets may offer a potential solution for individuals residing in regions with nutrient deficiencies as are a rich source of essential nutrients. More importantly, studies focused on the soil type of Baobab growth as well as regional and ecological differences contribute to the existing literature on Baobab tree products and their value, providing valuable insights for future research and dietary interventions that will be aligned with what was reported by [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, other comparable studies attributed C. olitorius as an inexpensive source of food nutrients due to the presence of vital nutrients such as iron, zinc, magnesium, calcium, copper, manganese, and molybdenum and potassium [56,60,58]. Comparing the nutrient composition of C. olitorius cultivated in South Africa and Ghana, nutrient content data revealed these leaves species had a similar quantity of zinc and iron [62].…”
Section: Mineral Contentmentioning
confidence: 93%
“…Several authors have concluded that L. taraxacifolia can serve as a functional food that can curb malnutrition and disease; two major problems confronting the developing countries after analysis of their nutritional qualities [48,59]. Several studies found it to be very rich in micronutrients and macronutrients like iron, manganese, zinc, magnesium, calcium, potassium, sodium and phosphorus [48, 35,60,61]. X. sagittifolium leaves supply a large amount of carbohydrates, calcium, copper, iron, magnesium, manganese, molybdenum, zinc phosphorus [38,56].…”
Section: Mineral Contentmentioning
confidence: 99%
See 1 more Smart Citation